The Effects of Investment Climate on Manufacturing Firms’ Growth in Uganda - Niringiye, Aggrey; Ogwal, Moses (TrustAfrica, 2013)
This study investigated the effects of investment climate on manufacturing firms’ growth in Uganda using pseudo panel data. The low and stagnant level of manufacturing in the Gross Domestic Product within most African countries has been widely recognized to be an important policy problem. This study adopted Gibrats Law of Proportionate Effect (LPE) and Learning model, due to Jovanovic, with some modifications to analyze investment climate factors that determine firm growth in Uganda. Results show that firm size, age, and average education are the main determinants of growth in a sample of Ugandan manufacturing firms. These results have important policy prescriptions to increase firm growth.